2020
DOI: 10.1029/2020ea001278
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Variations of Arctic Sea Ice From 2002 to 2017

Abstract: The variation of polar sea ice is an indicator of polar environmental change, which plays an important role in the study of regional and global climate change. In this paper, the latest sea ice data sets from the European Space Agency Climate Change Initiative were firstly combined to comprehensively analyze the spatial and temporal variation of Arctic sea ice concentration (SIC) and sea ice thickness (SIT) from 2002 to 2017. The results show that during this period, the SIC of the Kara Sea and the Barents Sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…One of the most obvious signs of the warming/changing Arctic is the changes in sea ice. Sea ice is rapidly decreasing in extent and concentration (Meier et al, 2014;Wang et al, 2020b), melting earlier, and freezing up later in the season (Markus et al, 2009;Wang et al, 2020b). The effects of these changes on the marine biogeochemistry and trace gas emissions are poorly known (Huntington et al, 2019), largely due to a lack of measurements.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most obvious signs of the warming/changing Arctic is the changes in sea ice. Sea ice is rapidly decreasing in extent and concentration (Meier et al, 2014;Wang et al, 2020b), melting earlier, and freezing up later in the season (Markus et al, 2009;Wang et al, 2020b). The effects of these changes on the marine biogeochemistry and trace gas emissions are poorly known (Huntington et al, 2019), largely due to a lack of measurements.…”
Section: Introductionmentioning
confidence: 99%
“…While the steepest satellite chlorophyll a concentration increase is typically observed in June, for the May 2019 event the steepest increase occurred in early May and mean chlorophyll a concentrations were higher than all previous May values and higher than all previous June values except 2015 (Figure 1). Previous studies have demonstrated that such anomalous events can offer natural experiments (e.g., Wang et al, 2020), revealing greater insights on bloom control in this dynamic and rapidly changing ecosystem. Here, we investigate underlying mechanisms that may have led to this exceptional event.…”
Section: Introductionmentioning
confidence: 99%
“…While the steepest satellite chlorophyll a concentration increase is typically observed in June, for the May 2019 event the steepest increase occurred in early May and mean chlorophyll a concentrations were higher than all previous May values and higher than all previous June values except 2015 (Figure 1). Previous studies have demonstrated that such anomalous events can offer natural experiments (e.g., Wang et al, 2020) (Sathyendranath et al, 2019). Sea ice concentration (SIC) contour lines shown are averaged over the same time period and computed from the NASA Team processing algorithm of the SMMR-SSM/I satellite record (Cavalieri et al, 1996).…”
mentioning
confidence: 99%
“…The East Siberian Sea (ESS) is one of the least studied subregions in the Arctic Ocean, although this region is experiencing the most rapid change in sea ice coverage, which could be partially attributed to recent Siberian heatwaves (Stroeve et al, 2012;Krumpen et al, 2019;Overland and Wang, 2020;Wang et al, 2020). In this perspective, we aim to quantify the effect of sea ice melting on the summertime CO 2 absorption capacity of the ESS, dependent on the degree of freshening and TA/DIC concentration and ratio of the sea ice.…”
Section: Introductionmentioning
confidence: 99%